Effects of Action Learning and Inquiry – Based Instructional Strategies on Secondary School Students’ Learning Outcomes in Physics (2012)
The importance of Physics in the development of science and technology has been emphasised in the literature.However, the enrolment and achievement of students in senior school certificate examination over the years keep dwindling as a result of the problem of selection of inappropriate and ineffective strategy of instruction and the abstract and practical nature of the subject, despite series of efforts of Physics educators and researchers aimed at addressing the issue.Thus, this study, therefore, investigated the effects of Action Learning Strategy (ALS) and Inquiry-Based Strategy (IBS),on secondary school students’ achievement in and attitude towards Physics. The study adopted the pretest-posttest, control group, quasi-experimental design, using a 3x3x2 factorial matrix. One hundred and Ninety-four senior secondary II students were purposively selected from six secondary schools in two local government areas of Kwara State as the sample. The six schools were randomly assigned to experimental and control groups. Six instruments were used in data collection, namely,Physics Attitude Questionnaire(r= 0.94), Achievement Test in Physics (r =0.76), Numerical Ability Test (r =0.77).Instructional Guide for Action Learning Strategy (experimental group I), Inquiry-Based Strategy (experimental group II) and Conventional Method (control group). Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance. Experimental treatment (that is, instructional strategies) had a significant main effect on students’ achievement in Physics (F (3,190) = 373.74; p<0.05) and attitude towards Physics (F (3,190) =106.19; p<0.05). Students exposed to ALS attained highest post-test mean score ( ̅=79.59) in achievement in Physics, followed by the IBS ( ̅= 56.16) and control group ( ̅= 26.49). Also, the ALS group had higher mean score ( ̅= 83.15), than the IBS ( ̅= 79.30) and the control group ( ̅= 56.90) on attitude towards Physics respectively. There is a significant effect of numerical ability on students’ achievement in Physics (F (3,190) =11.20; p<.05), and on their attitude towards Physics (F (3,190) =23.51; p<0.05). Students with high numerical ability had higher achievement score ( ̅=61.68) than those of the medium numerical ability ( ̅=53.21) and low numerical ability ( ̅= 47.90) students.Similarly, gender had a significant effect on students’ achievement in Physics (F(2,191) =10.52; p<0.05) but not on their attitude towards Physics. Female students had higher mean score ( ̅=56.95) than their male counterparts( ̅= 51.32).Action learning and Inquiry-based strategies were effective in enhancing students’ learning outcomes in Physics.The ALS particularly minimises the complexity of the Physics concepts.Therefore, Physics teachers should adopt the AL and IB strategies in enhancing students’ learning outcomes. These strategies may also increase students’ enrolment in Physics, particularly female students